1979
DOI: 10.1017/s0003356100042471
|View full text |Cite
|
Sign up to set email alerts
|

Milk production from diets of silage and dried forage. 3. Effect of formalin-treated ryegrass silage of high digestibility givenad libitumwith and without urea

Abstract: 1. Young adult and adult lactating British Friesian female cattle (heifers and cows) were individually fed ad libitum on perennial ryegrass silage (F) made with an additive of formic acid (3-41 of 85 % acid/t fresh grass) or on a silage (FF) made from the same crop with an additive of 9-01/t of a mixture of equal volumes of formic acid and formalin (35 % w/w solution of formaldehyde). Silage F was supplemented with a concentrate containing 50 % dried grass and 50 % barley at a low (L) or high (H) level of feed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

1981
1981
1997
1997

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 13 publications
(9 reference statements)
1
2
0
Order By: Relevance
“…When the primary growth silages used in the present trial were given to sheep as the sole feed, Siddons et al (1979) observed only a small depression in the proportion of cellulose digested in the rumen. These responses are in close agreement with those reported by Tayler et al (1979). The effect of the formic/HCHO mixture in reducing the digestibility of CP was greater in weeks 10 to 11 than in weeks 20 to 21, when the cows were given regrowth silage, and in this latter period the effect of the additive on the digestibility of DM and energy did not achieve significance.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…When the primary growth silages used in the present trial were given to sheep as the sole feed, Siddons et al (1979) observed only a small depression in the proportion of cellulose digested in the rumen. These responses are in close agreement with those reported by Tayler et al (1979). The effect of the formic/HCHO mixture in reducing the digestibility of CP was greater in weeks 10 to 11 than in weeks 20 to 21, when the cows were given regrowth silage, and in this latter period the effect of the additive on the digestibility of DM and energy did not achieve significance.…”
Section: Discussionsupporting
confidence: 90%
“…In the present trial the inclusion of soya bean meal in the concentrate increased the intake of both protein and DE by cows and this led to a 0.05 increase in milk energy output and an HOg/kg increase in protein yield during weeks 4 to 14 of lactation. However, since in this treatment (NA, HP) ME supply equated with ME output, it is unlikely that soya bean meal protein made no contribution to the supply of TP; and as Tayler et al (1979) have pointed out, care must be taken in the application to dairy cows of values determined with mature sheep. The supply of tissue protein (TP) to cows given silage NA with supplement LP equated with protein output, whilst in all other treatments TP supply was in excess of output (Table 7).…”
Section: Discussionmentioning
confidence: 99%
“…The data from GRI were compiled from six experiments conducted between 1974 and 1982 on animals selected from a herd of autumn-calving British Friesian dairy cows (Tayler & Aston, 1976;Tayler, Aston & Daley, 1979;Aston, Daley & Tayler, 1979;Thomas, Aston, Tayler, Daley & Osbourn, 1981;Thomas, Daley, Aston & Hughes, 1981 and unpublished data). In all, there were 19 treatments, each covering a period of time from a few weeks after calving until more than 14 weeks later in mid-lactation (Table 1).…”
Section: Description Of the Gri Datamentioning
confidence: 99%